Efisiensi Peraturan Mengenai Wajibnya Spin Off Pada Unit Usaha Syariah di Indonesia Menurut Perspektif Dallil Maslahah Mursalah - muhammad lazuardi Prihantono; raihan putri dahlan (ITB AAS INDONESIA Surakarta, 2023)
Spin off on the Sharia Business Unit is a government policy regarding new methods in the world of Islamic banking so that Islamic banks are more independent in carrying out Islamic banking activities in accordance with sharia principles. The presence of the spin off method in the Sharia Business Unit to reorganize the Sharia Business Unit to become an Islamic Commercial Bank has raised debate among experts. The implementation of spin offs in Sharia Business Units can reduce profits because several banks that are not ready to spin off will lose out in competition in the banking world. While the proopinion of the spin off policy is that spin off can increase adherence to sharia principles, improve quality in the form of assets, Third Party Funds (DPK), bank profits, as well as have a positive effect on the efficiency level of sharia banks. Therefore, this study discusses how to review maslahah mursalah in regulations regarding the mandatory spin off of Islamic Business Units. The research conducted by the author is an Islamic normative study with the maslahah mursalah approach. The technique of collecting data in this study was library research, namely using document study techniques and literature studies. The results of this study are the regulations regarding the mandatory Spin off in which Sharia Business Units must be implemented on the basis of maslahah mursalah because they are in accordance with the principles contained in maslahah mursalah.cetak miring).